Assessing Core Didactic Competencies of Pre-service English Language Teachers During Practicum: A European Perspective - Haggag, Haggag Mohamed (European Scientific Journal, ESJ, 2018)
This research discusses implementing a European document (European Portfolio of Student Teachers of Language EPOSTL) as a selfassessment tool. The research design experiments the European portfolio for pre-service language teachers (EPOSTL), which has been translated by the researcher and published by the Council of Europe. The portfolio is used with the aim of assessing the key teaching competencies of pre-service English language teachers during the teaching practice or the practicum. The paper examines key 5 descriptors of didactic competencies in the EPOSTL which are (Lesson planning- Conducting a lesson- classroom management- Independent learning- Assessment of learning). It highlights implementing the portfolios as means of assessing the competencies of language teachers in pre-service context. Instruments of the research include EPOSTL, teaching competence scale and portfolio assessment rubric. Results of implementing the portfolio on a sample of (N. 30) students at Hurghada Faculty of Education during their practicum (3 groups in 3 official language schools) are reported. The results indicate that using EPOSTL as a self-assessment tool has positive impacts on developing the five areas of the portfolio as measured by the Teaching Competencies Scale (TCS) designed by the researcher. The scale includes the main areas of the EPOSTL to be examined by the students while the fifth area "classroom management" was included as in the EPOSTL with "conducting a lesson" area. The recommendations include: implementing the electronic portfolios as self-assessment tools, the need for assessing didactic competencies using authentic assessment tools and designing valid and reliable tools of assessing the whole teaching practice or “practicum” of pre-service English language teachers.